The Effect of Education through Digital Media WhatsApp Auto Responding (WAR) on Knowledge about Anemia in Pregnant Women - Irawan, Andi Muh Asrul; Alfiah, Elma; Yusuf, Andi Mukramin; Kamilia, Nisrina; Sabililhaq, Muhammad Adnan; Harna, Harna; Putranto, Rudi Hendro; Fitrawan, Ahmad (Universitas Padjadjaran, 2023)
Anemia in pregnant women is still a problem in Parung Panjang village, Parung Panjang sub-district, Bogor district. The main cause is a lack of knowledge about the importance of iron for pregnant women. To address this problem, a quasi-experimental pre-posttest one group design study was conducted with a sample of 18 pregnant women and preconception women. The knowledge measurement tool used was a questionnaire. The measuring instrument used was a questionnaire on knowledge about anemia in pregnant women. The results showed a significant increase (p <0.05) in the knowledge of pregnant women and preconception women about anemia after the education and counseling activities were carried out, and they were enthusiastic and active in the discussion. The conclusion of this study is that the WhatsApp Auto Responding (WAR) media can be effectively used as one of the efforts to improve knowledge and prevent anemia in pregnant women in Parung Panjang village. The recommendation is to make education and counseling activities related to anemia using WAR a routine activity in Parung Panjang Village.Keywords: Anemia, auto responding, online education, pregnant women, WAR.